2018
DOI: 10.1007/s11606-017-4272-y
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Urban Health Primary Care Residency Tracks That Focus On Community-Level Structural Vulnerabilities

Abstract: We implemented two novel residency tracks that successfully placed graduates in community-based primary care settings. Integrating primary care training with experiences in community organizations can create primary care leaders and may foster collective efficacy among medical centers and community organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Several studies have shown that underrepresented minorities in medicine are more likely to treat underserved populations 14–16 . While this relationship has not been observed as robustly for females as it has in racial and ethnic minorities, this finding still speaks to the notion of minority groups taking a special interest in helping other minority groups; that urban programs often pioneer strong initiatives to aid underserved populations 17–19 might be particularly attractive to female applicants looking to aid groups that might need specialized care. Further, several studies have suggested that female residency applicants tend to value qualities that urban programs often emphasize 20 ; these values include diversity and equal representation in healthcare 21 .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown that underrepresented minorities in medicine are more likely to treat underserved populations 14–16 . While this relationship has not been observed as robustly for females as it has in racial and ethnic minorities, this finding still speaks to the notion of minority groups taking a special interest in helping other minority groups; that urban programs often pioneer strong initiatives to aid underserved populations 17–19 might be particularly attractive to female applicants looking to aid groups that might need specialized care. Further, several studies have suggested that female residency applicants tend to value qualities that urban programs often emphasize 20 ; these values include diversity and equal representation in healthcare 21 .…”
Section: Discussionmentioning
confidence: 98%
“…Advocacy is also difficult to teach and assess 30 . Lack of formal 7 , 8 , 11 , 19 , 21 , explicit 9 , 31 , and consistent 11 , 16 , 32 training leads to inadequate preparation 13 , 28 , 33 of trainees and negatively impacts patient care 13 . Perhaps most challenging for educators in this space has been the lack of formal curricula and guidelines to facilitate teaching efforts 15 17 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…1 ) IM residency-trained physicians who do not seek subspecialty training after residency may practice general outpatient IM (also called primary care), general inpatient IM (also called hospitalist medicine), or a combination of both. Published literature reveals several programs within IM residencies to provide training in underserved medicine (UM), including Montefiore Medical Center’s Residency Program in Social Medicine [ 11 ], University of California Davis’s Transforming Education and Community Health Program [ 12 ], Johns Hopkins University’s Urban Health Primary Care Residency Track [ 13 ], and Beth Israel Deaconess Medical Center’s HIV Primary Care Track [ 14 ], however most seek to produce PCPs. The University of Alabama at Birmingham published early information on its Health Disparities Track, which was available to all IM residents, however their small sample size limited program evaluation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%